Empowering the Purworejo Regional Leadership of 'Aisyiyah (PDA) as Paralegals and Mental Health Counselors - Indrawati, Septi; Risnawati Sasmita, Ajeng; Iftayani, Itsna; Choirunnisa, Bustania; Nawawi, Adin (Universitas Muhammadiyah Magelang, 2025)
Women in Purworejo Regency continue to face increasing violence, exploitation, and abuse due to various factors such as gender inequality, poverty, low education, and lack of awareness of their rights and position in society. Legal protection remains limited due to weak law enforcement and an ineffective judicial system. In response to these challenges, the Regional Leadership of 'Aisyiyah (PDA) Purworejo, as a women's autonomous organization under Muhammadiyah, aims to play a more active role in empowering and protecting women. This community service activity was designed to provide education and capacity-building to strengthen the role of ‘Aisyiyah leaders. The objectives were achieved through strategies such as training, mentoring, and community development. The main solution involved conducting paralegal and mental health counselor training for representatives of Branch Leadership of 'Aisyiyah (PCA) throughout Purworejo Regency, equipping them with legal and psychological knowledge to assist women in need.